Culture-Specific Norms Regarding High-Quality Use of Task Potential for Mathematical Learning—Contrasting Researchers’ Perspectives from Germany and Taiwan - Paul, Josephine F.; Dreher, Anika; Wang, Ting-Ying; Hsieh, Feng-Jui; Lindmeier, Anke (Journal für Mathematik-Didaktik, 2024)
Factors like the potential of tasks to support students’ mathematical learning and its use in instruction are consensually understood to be relevant for instructional quality across cultural contexts. Yet, research has also shown that perspectives on instructional quality may vary between cultural contexts. As an explanation, it is argued that such perspectives depend on instructional norms, which correspond to the expected behavior in instruction within a cultural context. Notably, research contrasting mathematics instruction from East Asian and Western cultures hints at potentially different instructional norms regarding high-quality use of task potential, but systematic evidence is lacking so far. This study addresses this gap and uses three text vignettes of instructional situations to systematically elicit and contrast instructional norms regarding the use of word problems for mathematical learning. Researchers from Germany (N = 17) and Taiwan (N = 19) evaluated the use of tasks in various instructional situations in an online survey, and their answers were qualitatively analyzed to determine possible culture-specific norms based on their reasoning. In two of the three cases, culture-specific norms in line with assumptions could be identified. In the third case, researchers in both countries referred to an interculturally shared instructional norm. Differences between the reasoning in answers from Germany and Taiwan indicate further cultural influences in line with assumptions based on prior research. We discuss the findings and their implications for the validity of intercultural research in mathematics education.
CRIS-Team Scopus Importer:2024-10-02
Keywords: Cross-cultural research; Cultural norms; Instructional norms; Intercultural validity; Quality of mathematics instruction